Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's simplify the expression \(\sqrt[4]{324 x^6 y^8}\) step by step.
1. Prime Factorize the Coefficient:
[tex]\[ 324 = 3^4 \times 4 \][/tex]
2. Break Down the Expression:
[tex]\[ 324 x^6 y^8 = (3^4 \times 4) x^6 y^8 \][/tex]
3. Split the Terms for easier simplification under the fourth root:
[tex]\[ \sqrt[4]{3^4 \times 4 \times x^6 \times y^8} \][/tex]
4. Simplify Each Part Under the Fourth Root:
- [tex]\[ \sqrt[4]{3^4} = 3 \][/tex]
- [tex]\[ \sqrt[4]{x^6} = x^{6/4} = x^{1.5} = x \cdot x^{0.5} = x \sqrt{x} \][/tex]
- [tex]\[ \sqrt[4]{y^8} = y^{8/4} = y^2 \][/tex]
- [tex]\[ \sqrt[4]{4} = \sqrt[4]{2^2} = 2^{1/2} = \sqrt{2} \][/tex]
5. Combine the Results:
[tex]\[ 3 \cdot x \cdot y^2 \cdot \sqrt[4]{4 x^2} \][/tex]
However, note that:
[tex]\[ \sqrt[4]{4 x^2} = \sqrt[4]{2^2 x^2} = (2x)^{1/2} = \sqrt{2x} \][/tex]
6. Simplify the Expression:
Combining the results together, we get:
[tex]\[ 3 x y^2 \sqrt[4]{4 x^2} \][/tex]
Therefore, the simplest form is:
[tex]\(\boxed{3 x y^2 \sqrt[4]{4 x^2}}\)[/tex]
1. Prime Factorize the Coefficient:
[tex]\[ 324 = 3^4 \times 4 \][/tex]
2. Break Down the Expression:
[tex]\[ 324 x^6 y^8 = (3^4 \times 4) x^6 y^8 \][/tex]
3. Split the Terms for easier simplification under the fourth root:
[tex]\[ \sqrt[4]{3^4 \times 4 \times x^6 \times y^8} \][/tex]
4. Simplify Each Part Under the Fourth Root:
- [tex]\[ \sqrt[4]{3^4} = 3 \][/tex]
- [tex]\[ \sqrt[4]{x^6} = x^{6/4} = x^{1.5} = x \cdot x^{0.5} = x \sqrt{x} \][/tex]
- [tex]\[ \sqrt[4]{y^8} = y^{8/4} = y^2 \][/tex]
- [tex]\[ \sqrt[4]{4} = \sqrt[4]{2^2} = 2^{1/2} = \sqrt{2} \][/tex]
5. Combine the Results:
[tex]\[ 3 \cdot x \cdot y^2 \cdot \sqrt[4]{4 x^2} \][/tex]
However, note that:
[tex]\[ \sqrt[4]{4 x^2} = \sqrt[4]{2^2 x^2} = (2x)^{1/2} = \sqrt{2x} \][/tex]
6. Simplify the Expression:
Combining the results together, we get:
[tex]\[ 3 x y^2 \sqrt[4]{4 x^2} \][/tex]
Therefore, the simplest form is:
[tex]\(\boxed{3 x y^2 \sqrt[4]{4 x^2}}\)[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.